New varieties of English in postcolonial literatures: Malaysian English in Malaysian literature in English - Abdul Rahman Ramakrishna, Rita (Curtin University, 2009)
This study investigates language choice in Malaysian literature written in English in three different phases of Malaysian sociopolitical development: the Immediate Post Independence Era (1957–1980), the Mahathir Era (1981–2002) and the Current Era (2003–2006).The study is organised around three major objectives. The first examines the development and the use of Malaysian English (MalE) by Malaysian writers; the second examines the extent to which the use of MalE relates to the sociocultural development in Malaysia; and the third explores the significance of shifts in writing style involving the use of localised English. The study identifies, categorises, and analyses instances of MalE in Malaysian literature in English in terms of these three overarching objectives.The outcomes of this study suggest that the use of a nativised endonormative variety of English in Malaysian postcolonial writings is becoming more prevalent, and that such a harnessing of linguistic resources by Malaysian writers has important ramifications in terms of the construction and maintenance of a shared Malaysian national identity.